Urinary exosomes: Potential biomarkers for diabetic nephropathy. Issue 12 (4th June 2020) - Sinha, Nisha; Kumar, Vivek; Puri, Veena; Nada, Ritambhra; Rastogi, Ashu; Jha, Vivekanand; Puri, Sanjeev
Abstract: Diabetic nephropathy is the most common diabetic complication culminating often into end‐stage renal disease. Classically, it is defined by the presence of albuminuria which has limited ability to be detected at early stages but deterioration in kidney function generally precedes albuminuria. This necessitates the development of newer diagnostic assays for diabetic nephropathy to determine the progression of the disease. Kidney associated diseases with non‐albuminuria further complicates a timely diagnosis and thus demands an early biomarker. Urinary exosomes, the nanovesicular entities are released by every epithelial cells of the nephron. Their protein or molecular cargo varies in the diseased state which may provide the pathophysiology of the kidney associated diseases. This drives them to be exploited as non‐invasive biomarker. This review thus integrates the recent findings on the significance of the urinary exosomes as diagnostic biomarker in kidney‐associated diseases, primarily in diabetic nephropathy. SUMMARY AT A GLANCE: This is short review of the potential of using urinary exosomes as a diagnostic tool in diabetic nephropathy at the proteomic and molecular level. It also provides a snapshot overview of current evidence in urinary exosomes in other form of kidney disease.